Characteristics of malignant tumors of digestive system and autoimmune diseases - Yin, Hang; Li, Qun (Frontiers in Genetics, 2023)
With the development of preoperative examination technology, endoscopic ultrasonography-guided fine-needle aspiration biopsy (EUS-FNA) has been widely used in preoperative pathological diagnosis. However, there are still challenges in obtaining appropriate tissue samples and obtaining accurate pathological results to predict the risk of disease. Therefore, this study aimed to analyze the characteristics of digestive system malignancies and their autoimmune diseases, and to analyze the clinicopathological features of pNEN with different pathological degrees. Analysis of CT image features to predict the pathological grade of pancreatic neuroendocrine tumors has become an important research topic in this field. The experimental results in this paper show that in multiphase CT examination, non-functioning pancreatic neuroendocrine tumors appear as peripheral clear hypervascular lesions. It is most clearly imaged at the end of the arterial phase and the portal venous phase, and the extent of local vascular invasion can be used as an indicator for assessing resectability. The sensitivity of CT examination is 63%-82%, and the specificity is 83%-100%, which varies according to its size.